Web performance testing of lecturer evaluation system (e-CEvas) applied with AJAX technology / Azmi Abu Seman, Nor Azlina Mahmud and Norfiza Ibrahim - Abu Seman, Azmi; Mahmud, Nor Azlina; Ibrahim, Norfiza (UiTM Cawangan Perlis, 2018)
Lecturer Evaluation System (e-CEvas) is used to measure lecturers’ strength and weaknesses every end of semester by the students. However, the current lecturer evaluation system had many problems such as slow performance, limited interactivity, loss of states and the data transmission had redundant code that was unnecessary in each page. To overcome those stated problem, AJAX technology is used to make the lecturer evaluation system much faster, easier to use, more reliable and increase the performance. This study applied AJAX technology in the development together with Visual Studio Ultimate 2012 as the editor, ASP.NET C# language for coding and SQL Server as the database. V-model framework approach was used in developing this research study which involves requirement analysis, system design, architectural design, module design, unit testing, integration testing, system testing and acceptance testing. Microsoft Visual Studio Web Performance and Load Testing software is used to measure the performance of AJAX technology and the result shows that differences of response time proved that AJAX is powerful web development technique for programming. User Acceptance Test was carried out to measure the satisfaction of users when using e-CEvas which the result shown that most respondents are agree to all instructions in the system and the organization of information on the screens is clear.